Horatio Bottomley and the far right before Fascism - Renton, Dave, 1972- author.
1 online resource (182 pages).
Keywords: "Horatio Bottomley and the Far Right Before Fascism examines Bottomley's life and politics, and what made him one of the great figures of Edwardian life. During the first world war, his magazine John Bull sold two million copies a week. Bottomley addressed huge crowds urging them to wage a war of extermination against ordinary Germans. The first chairman of the Financial Times, the inspiration for Toad in The Wind in the Willows, Bottomley was also a major figure in post-1918 politics, urging Conservative voters to dump their leaders and try something new. This carefully-researched biography, the first new life of Bottomley for 50 years, shows how he began on the centre-left of Edwardian politics, then moved to the margins, becoming a leading figure on the Edwardian far right, and pre-empting the non-fascist far right of our own days. This book will appeal to scholars and students with interests in political history, fascism and the far right"--